Reparations for Sexual and Gender-Based Crimes: A Premiere Applying an Intersectional Approach at the International Criminal Court? - Martin, Ana (IntechOpen, 2025)
Crimes of sexual and gender-based violence have experienced tremendous interest in international justice mechanisms and transitions from violence. Following their recognition and first convictions, gender justice is facing reparations as a new challenge that aims at effective remedies for victims. In the Ntaganda case, the International Criminal Court recently allocated reparations for girl soldier victims of rape and sexual slavery applying the principle of gender-sensitive reparations and stating that ‘intersectionality’ should be a core component. Intersectionality is a human rights-based approach to understand the structural dynamic of discrimination underpinning gross violations against marginalized groups in order to obtain an effective remedy. This chapter answers the question whether the International Criminal Court is entitled to and is effectively applying an intersectional approach to reparations for crimes of sexual and gender-based violence in what amount would be true to engagement with effective remedies tackling the root causes of gross violations.
Keywords: sexual and gender-based violence, reparations, intersectionality, child soldiers, international crimes, human rights